TRAVELERS’ MOTIVATIONS TO TRAVEL ABROAD DURING COVID 19 OUTBREAK - Iin Rachmawati; Kumiko Shishido (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Purpose: The purpose of this study is to know the impact of Covid 19 to travel desire of those Indonesian travelers to travel abroad. Research methods: This study used mix methods to give details on the data which was produced by the media related to this corona virus or more recently popular as Covid 19. The data has been gathered in the form of numbers and tables about the spread of Covid 19 over the world, about the victims infected by this virus over the last three months, as well as about the direct impact on the tourism sector for Indonesian travelers to travel abroad. Then, the data has explained descriptively in order to get deeper understanding about Covid 19 facts and travel impact towards Indonesian travelers. Results and discussions: The result showed that the spreading has happened almost in the entire world with most infected area is around Asia and Europe with the total case of 245,612. The death victims are 10,048 people and the survivors are 88,437 people. The data statistics are also showed for about 78% Indonesian travelers chose to cancel and reschedule their travel plans to abroad as well as 22% of them still have no idea what to do with their future trip. Conclusion: It can be concluded that Covid 19 has hit the tourism sector in Indonesia